INVESTIGATION OF THE PRESERVATION TECHNIQUES FOR PERISHABLE FOOD COMMODITIES THROUGH A COMPARATIVE STUDY OF OKRA, TOMATO, AND FISH - Oshomogho, Frederick; Idah, Paul Anosi (FUDMA Journal of Sciences, 2026)
Postharvest spoilage of perishable crops such as okra (Abelmoschus esculentus), tomato (Solanum lycopersicum), and fish (Clarias gariepinus) contributes to significant food loss and reduced nutritional availability in Nigeria. This study aimed to evaluate controlled oven-drying as a preservation method for these commodities and examined changes in their nutritional composition during storage. Samples were dried at 60°C to ensure uniform heat transfer and minimize oxidative degradation. Moisture, protein, carbohydrate, and vitamin C contents were determined using standard analytical methods. Drying kinetics were assessed using first-order reaction models, and activation energy (Ea) for moisture diffusion was calculated using the Arrhenius equation. Drying significantly reduced the moisture content of all samples, improving shelf life and limiting microbial activity. Protein content increased slightly in fish (24.72–25.61%), okra (2.73–2.75%), and tomato (1.62–1.65%) due to concentration effects. Vitamin C showed substantial losses of 40–80%, confirming its thermolabile nature, while carbohydrate levels remained largely stable. Fish exhibited clear first-order drying behaviour, with rate constants of 0.0153, 0.0189, and 0.0191 min⁻¹ at 60°C, 80°C, and 100°C, respectively. The activation energy of 6.093 kJ/mol indicated moderate energy requirements and suggested moisture removal mainly through surface evaporation with limited internal diffusion. Overall, the results show that moderate drying temperatures, particularly around 60°C, can preserve key nutrients while enhancing product stability, making this method suitable for processing perishable foods in tropical environments. Higher temperatures, such as 100°C, increase moisture loss but accelerate nutrient degradation.
Keywords: Drying; Moisture content; food preservation; kinetics; Activation energy